Makanan Sattvika dan Pengaruhnya Terhadap Kesehatan dan Karakter - Ayu Veronika Somawati; Komang Surya Adnyana (Jurnal Yoga dan Kesehatan, 2020)
Being born as a human is a virtue in Hinduism, because among all living things only humans are gifted with the ability to think and distinguish good and bad deeds, and can help themselves from repeated births and deaths towards the ultimate goal of Hinduism. itself namely "Moksartham Jagadhita ya ca iti dharma". Because the primacy of birth as a human being, of course this opportunity must be very grateful and utilized as well as possible. One way that humans can do as a form of gratitude to Ida Sang Hyang Widhi Wasa for birth as a human being is to maintain the healthy body. With a healthy and well-maintained body, surely a person will be able to work at maximum capacity Eating is not an activity to put food into the mouth carelessly and not measured. Eating in question is how a person is able to maintain the intake of food that enters his body properly and correctly so that what is eaten can function optimally for the health of the body. Judging from the science of nutrition, of course this will be associated with intake of carbohydrates, proteins, minerals, fats and others that enter the body. But when viewed from the teachings of Hinduism, regulating food patterns and intake of food that enters the body is also contained in Hindu religious literature, one of which is contained in the Bhagavad-gītā scriptures. And after further study, it can also be understood that what is eaten will ultimately affect one's mindset and character. By using descriptive methods, this paper will examine good food for body health (sattvika food) and its effect on someone's character.